Comparison of Breastfeeding and Formula Milking on the Growth of Newborn Babies in Merauke Regional Hospital in 2023 - Yenny Meigie Diana Talohanas; Tri Hastuti; Hans Angelius Suharto; Mifthakul Muslichmah (Universitas STRADA Indonesia, 2024)
Breast milk (breast milk) is a fluid secreted by the mother's breast glands in the form of natural food or the best, nutritious and high-energy milk produced during pregnancy. Breastfeeding is important for a baby's growth. Mothers who have babies must provide breast milk for 6 months and cannot provide complementary foods with breast milk. After 6 months, as a companion for optimal growth, they can be given formula milk. The aim of this research is to determine the comparison of breastfeeding and formula milk feeding to newborns within the Merauke District Hospital. The research design used is an analytical observational method with an approach cross sectional. The number of samples in this study was 60 mothers who had newborn babies with a ratio of 30:30. The research was conducted from November to December 2023. The majority of mothers were in the age range 26 – 35 years, namely 37 respondents (761.6%), that the proportion of respondents who did not work was greater than respondents who worked, namely 66.6% compared to 33.3%, the majority (38 people or 63.3%) had a high school education. Showing normal growth were 50 babies (83.3%) and those who did not experience normal growth were 10 babies (16.6%). Most abnormal growth occurs in newborn babies, one of which is excessive weight gain due to excessive intake of formula milk from the start of the baby's birth. Comparison of breastfeeding and formula milk on the growth of newborn babies based on statistical tests using tests Chi-Square The results obtained were p = 0.000 < 0.05, so there was a significant comparison between breastfeeding and formula milk on the growth of newborn babies at the Merauke District Hospital in 2023.